Method of provocative group discussion to study the value-affective polarization of a social group - A.N. Lebedev (Экспериментальная психология)
Context and relevance. The article describes the method of provocative group discussion, which was developed to study the phenomenon of value-affective polarization of a social group. This method is based on the classic version of the focus group discussion, proposed in the 50s of the twentieth century by R. Merton and widely used today both for solving practical problems and for sociological and socio-psychological research. Methods and materials. The article provides a comparative analysis of both methods. Some questions of validity and reliability of the method of provocative group discussion are considered, which are illustrated by references to empirical data. The peculiarity and novelty of the method consists in changing the goals and objectives of the study, a fundamentally different strategy of moderator behavior and a significant increase in the role of independent experts analyzing the interaction of participants when discussing topics that cause value-affective polarization of the group. Results. It is shown that the proposed method can be used not only to study the polarization of a group, but also to study how it affects large groups of respondents. In particular, the involvement of experts or so-called "observers" (up to several hundred) turns the method into a convenient tool for quantitative study of the dynamics of opinions.